Pričevanja otrok aleksandrink o življenju v Egiptu v prvi polovici 20. stoletja - Koprivec, Daša (Etnolog. Nova vrsta (Ljubljana), 2009)
The article presents the stories of two generations of children of the Alexandrian Women about life in Egypt. The first generation was born in Goriška in 1922-1929, the second in Egypt 1937-1948. The children born in Goriška were aged six to ten when they joined their mothers who had emigrated to work in Egypt. The article wishes to draw attention to the family life of the Alexandrian Women in Egypt in the first half of the 20th century. Their children, now aged between 63 and 87, are important witnesses to life in Egypt since they spent several decades of their life in the country. The author has collected stories from people who now live in Goriška as well as from people living in Australia, Canada, Italy, or Switzerland.
Keywords: Koprivec, Daša, 1964-; ethnology; etnologija; ljudsko življenje; aleksandrinke; slovenske izseljenke; Slovenes; Slovenke; potomci; emigracija; Egipt; Egypt; zgodovinski pregledi